2009
DOI: 10.1016/j.contraception.2008.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Unmet need for contraception among sex workers in Madagascar

Abstract: Background The study was conducted to investigate past and future pregnancy preferences and contraceptive need among Malagasy sex workers. Study Design We analyzed data on pregnancy and contraceptive use collected during the baseline visit of a randomized, prospective formative trial which assessed diaphragm and microbicide acceptability among sex workers. To be eligible, women could not be pregnant or planning pregnancy for the next 2 months. Results Women (N=192) from four cities (Antananarivo, Antsirana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
60
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 21 publications
8
60
1
1
Order By: Relevance
“…This work builds on earlier, mostly secondary, analyses of the contraceptive needs of FSWs [4][5][6] . The only other mixed-method, primary study of the unmet needs of FSWs of which the authors are aware was conducted in Southeast Asia 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This work builds on earlier, mostly secondary, analyses of the contraceptive needs of FSWs [4][5][6] . The only other mixed-method, primary study of the unmet needs of FSWs of which the authors are aware was conducted in Southeast Asia 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported on pregnancy desires and contraceptive use among FSWs. The limited amount of existing research has shown high incidences of unintended pregnancy and a low contraceptive prevalence in this particular group [3][4][5][6] . All studies report that sex workers who do use contraception resort most often to condoms yet the latter are not consistently used in all sex acts 3,[5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lifetime prevalence of abortion among female sex workers in Asia and Africa ranges from 22% to 86%, [6][7][8][9][12][13][14] suggesting that sex workers' pregnancies frequently are unintended. These high rates of abortion should not be surprising, considering the burdens that pregnancy may pose to such women.…”
mentioning
confidence: 99%
“…Female sex workers may use condoms inconsistently because they lack the autonomy to insist on condom use with husbands, boyfriends or other steady partners, agree to have condomless sex with clients who will pay extra, are unable to negotiate condom use with clients and or are forced to have sex. [6][7][8][9][10][11] Using condoms inconsistently, rather than every time, increases the risk not only of acquiring an STI, but also of pregnancy if a second contraceptive method is not used.…”
mentioning
confidence: 99%